DESCRIPTION OF CASES OF ACCIDENTAL EXOGENOUS POISONING IN THE MUNICIPALITY OF ANÁPOLIS-GO (CIPEEX, 2026)
INTRODUCTION: The rational and safe use of medications is essential and should be reinforced by healthcare professionals. Events are classified as accidents, suicides, criminal acts, and other causes. The most common symptoms are vomiting, tachycardia, sweating, diarrhea, respiratory disorders, and sedation. Drug poisoning is a public health problem and requires mandatory reporting. OBJECTIVE: To describe the epidemiological profile, evolution, and prevalence of cases of accidental exogenous poisoning by prescription and self-medication medications in Anápolis, Goiás, Brazil, between 2014 and 2024. METHOD: This is an observational, descriptive, cross-sectional, and retrospective epidemiological study conducted with secondary data obtained from DATASUS. Quantitative statistical analysis was performed using the chi-square test and simple frequency. RESULTS: There were 413 confirmed cases. Children aged 0-9 years were most affected (85.5%), followed by adolescents (10-19 years, 5.3%). The distribution was balanced between the sexes (50.8% female, 49.2% male). Mixed-race individuals were the majority (72.4%). Clinical evolution showed recovery without sequelae in 98.3%, while 0.8% died. These findings reinforce the need for prevention through educational campaigns, safe storage, and public policies aimed at the rational use of medications. CONCLUSION: Despite the low mortality rate, the epidemiological impact is significant and requires intersectoral prevention actions.
Keywords: Poisoning; Medications; Prescription Drug Misuse